Stink and the world's worst super-stinky sneakers - McDonald, Megan; Reynolds, Peter, 1961- (Cambridge, Mass. : Candlewick Press, 2007)
A class visit to the Gross-Me-Out exhibit at the science museum inspires Stink Moody to create a variety of terrible smells to put on the sneakers he plans to enter in the World's Worst Super-Stinky Sneaker contest.
Keywords: Smell -- Juvenile fiction; Contests -- Juvenile fiction; Humorous fiction